Menghitung Eco-efficiency di PT. APIE Indo Karunia - Lay, William Sutomo; Panjaitan, Togar W.S. (Jurnal Titra, 2014)
PT. APIE Indo Karunia produces is a casting company that produces steel and ironpart such as gear. The casting processes include material melting, mold making process usingsilica sand, moldcoating process, and pouring the melted metal into the mold. These processesuse a huge amount of energy that affect to environment. Thus, the calculation of eco-efficiencyratio for PT. APIE Indo Karunia is needed.The eco-efficiency ratio in months February, March and April are 1,06, 1,15 and 1,09respectively. While, the eco-efficiency of the total production on energy consumption are 1,22, 1,2and 1,226. These values are higher than the Indonesian energy eco-efficiency which valued 0,46.It means that the production process of PT. APIE Indo Karunia is still inefficient in terms ofenergy consumption .